Negotiating empowerment : studies in English language education - Dheram, Prema Kumari, 1956-; Indo-American Centre for International Studies (Hyderabad, India) (Hyderabad : Orient Longman, 2008)
Contributed articles presented at an international conference held at Indo-American Centre for International Studies, Hyderabad, India in 2004.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching -- South Asia -- Congresses; English language -- Study and teaching -- Congresses